2022
DOI: 10.21037/atm-22-3340
|View full text |Cite
|
Sign up to set email alerts
|

Identification of molecular subtypes in lung adenocarcinoma based on DNA methylation and gene expression profiling—a bioinformatic analysis

Abstract: Background: Molecular typing based on deoxyribonucleic acid (DNA) methylation and gene expression can extend understandings of the molecular mechanisms involved in lung adenocarcinoma (LUAD) and enhance current diagnostic, treatment, and prognosis prediction approaches.Methods: Gene expression and DNA methylation data sets of LUAD were obtained from The Cancer Genome Atlas (TCGA), and the differential gene and methylation expression levels were analyzed.Results: We successfully divided the LUAD samples into 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Methylation can change the activity of a DNA segment without changing the sequence. When located in a gene promoter, DNA methylation typically acts to repress gene transcription 52,53 . Consequently, DNA methylation has a role in carcinogenesis.…”
Section: Methods ‐ Search Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Methylation can change the activity of a DNA segment without changing the sequence. When located in a gene promoter, DNA methylation typically acts to repress gene transcription 52,53 . Consequently, DNA methylation has a role in carcinogenesis.…”
Section: Methods ‐ Search Strategymentioning
confidence: 99%
“…When located in a gene promoter, DNA methylation typically acts to repress gene transcription. 52 , 53 Consequently, DNA methylation has a role in carcinogenesis. Bi et al investigated the DNA methylation status of A and B thymomas.…”
Section: Methods ‐ Search Strategymentioning
confidence: 99%
“…For instance, Tang et al . showed that two metabolism‐related genes (MRGs), ASNS and BLVRA were strongly correlated with survival in TET, 164 and Hou et al . revealed that lower expression of HMGB1, a proinflammatory cytokine‐related gene, is seen in thymic carcinomas compared to thymoma, and correlates with a poor prognosis 165 .…”
Section: Prognostic Factorsmentioning
confidence: 99%
“…163 Gene expression profiling may also be correlated with prognosis. For instance, Tang et al showed that two metabolismrelated genes (MRGs), ASNS and BLVRA were strongly correlated with survival in TET, 164 and Hou et al revealed that lower expression of HMGB1, a proinflammatory cytokine-related gene, is seen in thymic carcinomas compared to thymoma, and correlates with a poor prognosis. 165 Higher mutation rates have been seen with advanced stage and more advanced pathological types.…”
Section: Prognostic Factorsmentioning
confidence: 99%